POLITIK HUKUM MENEGAKKAN KONSTITUSI Tinjauan Status Dwi Kewarganegaraan Berdasarkan Undang-Undang No. 12 Tahun 2006 - Nurlely Darwis (UNIVERSITAS DIRGANTARA MARSEKAL SURYADARMA, 2016)
Indonesian political spirit of citizenship law is to ensure the ownership status of citizens for everyone, but exclusively a fixed priority to the interests of the nation and the people of Indonesia. And that is why Indonesia is adopting a single citizenship with dual-citizenship tolerance is limited. That translated into legal politics of Indonesian nationalism nationality Indonesia at that time. Even if nationalism is now regarded as no longer relevant and needs to be repaired again, of course it can be done, because the law is an agreement or in other words the resultant of every situation and condition.